Pengendalian Kualitas Produk Standar Motor Type K0Wl Menggunakan Metode Seven Tools dan Kaizen Untuk Mengurangi Tingkat Kecacatan Produk Di Pt. Guna Senaputra Sejahtera - MAULANA, ANTONI; Maulana, Aji (Universitas Pamulang, 2025)
This study aims to analyze the causes of product defects and evaluate the effectiveness of continuous improvement actions in the production process at PT. Guna Senaputra Sejahtera to reduce defect levels in accordance with company quality targets. The research applies a quality control approach using the Seven Tools integrated with the Kaizen method. The Seven Tools are used to identify defect types and causes through check sheets, histograms, Pareto diagrams, and cause-and-effect diagrams, while Kaizen is used to formulate and implement continuous improvement actions. The data were obtained from historical production records from May 2024 to October 2025. The results show that Kaizen-based improvements significantly reduced product defect levels, from 8.47% in April to an average of 2.62% during July–October, resulting in a reduction of 5.84%, exceeding the company’s target of 5%. Keywords: Quality Control, Seven Tools, Kaizen.